Intrapersonal strengths and interpersonal support: predicting academic buoyancy through psychological capital and growth mindset - Xiao, Gui; Liu, Huifang (Frontiers in Psychology, 2025)
IntroductionThis mixed-methods study, situated within the framework of personality and social psychology, examines the interplay of psychological capital, social support, and growth mindset in predicting academic buoyancy among undergraduate English majors across three universities in mainland China.MethodsIn the quantitative phase, established instruments were utilized to assess direct and mediated relationships among 516 undergraduate English majors, analyzed via structural equation modeling. The qualitative phase involved semi-structured interviews with 18 students to offer richer insights into these dynamics, analyzed using thematic analysis.ResultsThe quantitative analysis revealed that psychological capital and social support significantly and directly predict academic buoyancy (β = 0.413 and β = 0.341, respectively, p < 0.001). Furthermore, growth mindset was identified as a significant mediating variable in these associations (indirect effects: β = 0.098 and β = 0.126, p < 0.001). The proposed model accounted for 51% of the variance in academic buoyancy. Thematic analysis of qualitative data identified four core themes: navigating academic challenges, leveraging a growth mindset, the protective influence of social support, and the development of psychological capital.DiscussionStudent narratives provided vivid accounts of overcoming academic obstacles, illustrating the mechanisms by which psychological capital and social support enhance adaptive beliefs and academic buoyancy. The findings underscore the importance of interventions designed to strengthen psychological capital, cultivate growth mindsets, and enhance social support networks within educational contexts.